Survey of the difficulty-composition relation with the ensembles in rhythmic gymnastics - Gantcheva, G. (Research in Kinesiology, 2017)
The structure of the competitive routines is an important part of the preparation in the gymnastics events. In order to survey the composition structure of the ensemble routines, we analyzed the routines of three teams, which have won a quota for the Olympics-2016, regarding the number of the difficult exercises, the artistic part of the routines, and a comparison of the starting and obtained score in competition. Analytical-synthetic method was used. The visual analysis of the routines gives an idea of the artistic side of the compositions, of spectacle and attractiveness of the competitive routines, in relation with the strong sides and traditions of the particular gymnastics school. The obtained score is within the range of 86-95% and is an important component in the final ranking. The results from the present study could be used as a point of reference in the teams` determining their strategy for creating competitive routines.